Relations and Resistance of Authorities in Deforestation of Indigenous Forests in Kinipan Village, Central Borneo - Kartika, Ema; Nafisah, Jazilatun; Dzikrillah, Nurfaizzatu; Azkia, Rizka Noor; Kusumaningtyas, Zahra; Pramono, Didi (Universitas Muhammadiyah Surakarta, 2023)
The Kinipan Indigenous Forest is both a livelihood and a vital habitat for indigenous peoples, animals, and plants. However, the presence of corporates has caused issues that have upset the equilibrium of the Kinipan Customary Forest. This research seeks to analyze the pattern of interactions that led to the admission of corporations into customary forests and to identify the resistance of the indigenous Kinipan people. Qualitative approach was employed, including observation collection techniques and data documentation from a Watchdoc Documentary-uploaded documentary video titled